Desert particulate matter from Afghanistan increases airway obstruction in human distal lungs exposed to type 2 cytokine IL-13 - Cervantes, Diana; Schaunaman, Niccolette; Downey, Gregory P.; Chu, Hong Wei; Day, Brian J. (Frontiers in Medicine, 2023)
Deployment related asthma-like symptoms including distal airway obstruction have been described in U.S. military personnel who served in Iraq and Afghanistan. The mechanisms responsible for the development of distal airway obstruction in deployers exposed to desert particulate matter (PM) is not well understood. We sought to determine if respiratory exposure to PM from Afghanistan (PMa) increases human distal airway hyperresponsiveness (AHR) with or without exposures to IL-13, a type 2 cytokine. We further tested whether mitochondrial dysfunction, such as ATP signaling and oxidative stress, may contribute to PMa-mediated AHR. Precision-cut lung slices from donors without a history of lung disease, tobacco smoking, or vaping were pre-treated with IL-13 for 24 hours. This was followed by exposure to PMa or PM from California (PMc, control for PMa) for up to 72 hours. The role of hydrogen peroxide and ATP in AHR was assessed using the antioxidant enzyme catalase or an ATP receptor P2Y13 antagonist MRS2211. AHR in response to methacholine challenges as well as cytokine IL-8 production were measured. PMa alone, but not PMc alone, trended to increase AHR. Importantly, the combination of PMa and IL-13 significantly amplified AHR compared to control or PMc+IL-13. PMa alone and in combination with IL-13 increased IL-8 as compared to the control. PMa increased H2O2 and ATP. MRS211 and catalase reduced AHR in PCLS exposed to both PMa and IL-13. Our data suggests that PMa in a type 2 inflammation-high lung increased AHR in part through oxidative stress and ATP signaling.